2017
DOI: 10.1016/j.crwh.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Urinary ascites in late onset of bladder injury post laparoscopic hysterectomy

Abstract: Urinary tract injuries are unfortunate complications of pelvic surgery. With the increasing popularity of minimally invasive surgery, a thorough understanding of electrosurgical instrumentation and their thermal spread is important to reduce patient injuries.The index patient was a 50 year old woman who underwent a supracervical hysterectomy 5 years prior to her presentation with pelvic pain and dysuria. When her symptoms failed to improve despite antibiotic and analgesic therapy, an abdominal CT scan revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Dawkins et al reported a case of urinary ascites 5 years after laparoscopic hysterectomy during which a thermal injury was observed in routine intraoperative cystoscopy. 5 Patient underwent bladder decompression for 10 days and CT urography did not reveal any pathology at the 10th postoperative day. 5 years later she presented with the complaints of dysuria and abdominal pain.…”
Section: Discussionmentioning
confidence: 98%
“…Dawkins et al reported a case of urinary ascites 5 years after laparoscopic hysterectomy during which a thermal injury was observed in routine intraoperative cystoscopy. 5 Patient underwent bladder decompression for 10 days and CT urography did not reveal any pathology at the 10th postoperative day. 5 years later she presented with the complaints of dysuria and abdominal pain.…”
Section: Discussionmentioning
confidence: 98%
“…A vesico-peritoneal fistula is a rare condition. [1][2][3][4] Abdullah reported this entity in a 48-year-old female with history of laparoscopic hernia repair with composite mesh three years before the diagnosis. 2 Ooi and Ismail described it in two female patients with emergency cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have compared outcomes in surgical management of bladder defect in benign enterovesical fistulas in the long term, closure of the bladder wall does not appear to have different outcomes in the short term. 3 The 5-year interval between etiology and diagnosis could be explained by a urinary bladder diverticulum formation and rupture, adhesions of the fistulous tract limiting leakage, and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations